CORRELATION OF ANEMIAN AND PREMATUR LABOUR IN ISLAMIC HOSPITAL PKU MUHAMMADIYAH SINGKIL - Ika Esti Anggraeni; Ike Putri Setyatama; Masturoh Masturoh (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
Anemia increases the risk of maternal death during pregnancy, due to the low blood supply resulting in disruption of body cell function and resulting in premature labor. Based on Riskesdas in 2018, about 48.9% of pregnant women had anemia. Preterm labor was the leading cause of neonatal morbidity and mortality in the world. In 2018, Tegal Regency had 10% maternal death caused by anemia. There was a 5.4% mother with anemia and 5.2%, premature babies, in PKU Muhammadiyah Singkil. This study aimed to determine the correlation of anemia with premature labor at PKU Muhammadiyah Singkil. This study was a quantitative study used analytic method with a retrospective research design. This study was conducted in Islamic Hospital PKU Muhammadiyah Singkil using medical records of 70 pregnant women. The data were taken from August-October 2018. Collected data analyzed using bivariate analysis. The study finding shows that 54% of respondents suffered anemia, and 55.7% had preterm labor. The bivariate analysis shows a p-value = 0.0001, which means there is a significant correlation between anemia and preterm labor. There is 0.73 times more risk of incidence in preterm labor in pregnant women with anemia.Keywords: Anemia, Premature Labor